Experimental intoxication by the leaves of Melia azedarach (Meliaceae) in cattle - Méndez González, María del Carmen (2002)
Green leaves of Melia azedarach were administered at single doses ranging from 5 to 30 g/ kg bw to 11 calves. Clinical signs were depression, ruminal stasis, dry feces with blood, ataxia, muscle tremors, sternal recumbency, hypothermia and abdominal pain. Serum AST and CPK were increased. Signs appeared from 8 to 24 hours after dosing, and the clinical course lasted from 2 to 72 hours. Three calves dosed with 30g/kg bw died. The macroscopic findings included intestinal congestion, yellow discoloration of the liver, brain congestion and dry feces with blood in the rectum. The liver showed swollen and vacuolated hepatocytes. Necrotic hepatocytes were scattered throughout the parenchyma or concentrated in the periacinar zone. Degenerative and necrotic changes were observed in the epithelium of the forestomachs. There was also necrosis of the lymphoid tissue. Skeletal muscles showed hyaline degeneration and fiber necrosis. The necrotic fragments contained floccular or granular debris with infiltration by macrophages and satellite cells.